Investigation of laser-induced periodic surface structures using synthetic optical holography - Gurevich, Evgeny L.; Hofmann, Martin R.; Gerhardt, Nils Christopher; Neutsch, Krisztian (Nanomaterials)

Low-cost Sensor System for on-the-field Water Quality Analysis - Petrov, Dmitry; Taron, Kim-Florian; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (2021 Smart Systems Integration (SSI))

Local Power Control using Wireless Sensor System for Microgrids in Africa - Hilleringmann, Ulrich; Petrov, Dmitry; Mwammenywa, Ibrahim; Kagarura, Geoffrey Mark (2021 IEEE AFRICON)

Microcontroller Firmware Design for Industrial Wireless Sensors - Petrov, Dmitry; Kroschewski, Konstantin; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))

Low-Power Primary Cell with Water-Based Electrolyte for Powering of Wireless Sensors - Petrov, Dmitry; Hilleringmann, Ulrich (Advances in Science, Technology and Engineering Systems Journal)

Low-Cost NB-IoT Microgrid Power Quality Monitoring System - Petrov, Dmitry; Kroschewski, Konstantin; Mwammenywa, Ibrahim; Kagarura, Geoffrey Mark; Hilleringmann, Ulrich (2021 IEEE Sensors)

Time-resolved photoluminescence characterization of InGaAs/GaAs nano-ridges monolithically grown on 300 mm Si substrates - Shi, Yuting; Kreuzer, Lisa C.; Gerhardt, Nils Christopher; Pantouvaki, Marianna; Van Campenhout, Joris; Baryshnikova, Marina; Langer, Robert; Van Thourhout, Dries; Kunert, Bernardette (Journal of Applied Physics)
The monolithic growth of III–V materials directly on Si substrates provides a promising integration approach for passive and active silicon photonic integrated circuits but still faces great challenges in crystal quality due to misfit defect formation. Nano-ridge engineering is a new approach that enables the integration of III–V based devices on trench-patterned Si substrates with very high crystal quality. Using selective area growth, the III–V material is deposited into narrow trenches to reduce the dislocation defect density by aspect ratio trapping. The growth is continued out of the trench pattern and a box-shaped III–V nano-ridge is engineered by adjusting the growth parameters. A flat (001) GaAs nano-ridge surface enables the epitaxial integration of a common InGaAs/GaAs multi-quantum-well (MQW) structure as an optical gain medium to build a laser diode. In this study, a clear correlation is found between the photoluminescence (PL) lifetime, extracted from time-resolved photoluminescence (TRPL) measurements, with the InGaAs/GaAs nano-ridge size and defect density, which are both predefined by the nano-ridge related pattern trench width. Through the addition of an InGaP passivation layer, a MQW PL lifetime of up to 800 ps and 1000 ps is measured when pumped at 900 nm (only QWs were excited) and 800 nm (QWs + barrier excited), respectively. The addition of a bottom carrier blocking layer further increases this lifetime to ∼2.5ns (pumped at 800 nm), which clearly demonstrates the high crystal quality of the nano-ridge material. These TRPL measurements not only deliver quick and valuable feedback about the III–V material quality but also provide an important understanding for the heterostructure design and carrier confinement of the nano-ridge laser diode.

Spin-lasers: spintronics beyond magnetoresistance - Žutić, Igor; Xu, Gaofeng; Lindemann, Markus; Faria Junior, Paulo E.; Lee, Jeongsu; Labinac, Velimir; Stojšić, Kristian; Sipahi, Guilherme M.; Hofmann, Martin R.; Gerhardt, Nils Christopher (Solid State Communications)
Introducing spin-polarized carriers in semiconductor lasers reveals an alternative path to realize room-temperature spintronic applications, beyond the usual magnetoresistive effects. Through carrier recombination, the angular momentum of the spin-polarized carriers is transferred to photons, thus leading to the circularly polarized emitted light. The intuition for the operation of such spin-lasers can be obtained from simple bucket and harmonic oscillator models, elucidating their steady-state and dynamic response, respectively. These lasers extend the functionalities of spintronic devices and exceed the performance of conventional (spin-unpolarized) lasers, including an order of magnitude faster modulation frequency. Surprisingly, this ultrafast operation relies on a short carrier spin relaxation time and a large anisotropy of the refractive index, both viewed as detrimental in spintronics and conventional lasers. Spin-lasers provide a platform to test novel concepts in spin devices and offer progress connected to the advances in more traditional areas of spintronics.

Confocal laser scanning holographic microscopy of buried structures - Schnitzler, Lena; Neutsch, Krisztian; Schellenberg, Falk; Hofmann, Martin R.; Gerhardt, Nils Christopher (Applied Optics)
In this paper, we present a confocal laser scanning holographic microscope for the investigation of buried structures. The multimodal system combines high diffraction limited resolution and high signal-to-noise-ratio with the ability of phase acquisition. The amplitude and phase imaging capabilities of the system are shown on a test target. For the investigation of buried integrated semiconductor structures, we expand our system with an optical beam induced current modality that provides additional structure-sensitive contrast. We demonstrate the performance of the multimodal system by imaging the buried structures of a microcontroller through the silicon backside of its housing in reflection geometry.

Water-based primary cell for powering of wireless sensors - Petrov, Dmitry; Hilleringmann, Ulrich (2020 IEEE SENSORS)

Doctor blade system for the deposition of thin semiconducting films - Petrov, Dmitry; Meyers, Thorsten; Reker, Julia; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Wireless power supply for a RFID based sensor platform - Schmidt, Marco; Petrov, Dmitry; Hedayat, Christian; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

RFID based sensor platform for industry 4.0 application - Petrov, Dmitry; Schmidt, Marco; Hilleringmann, Ulrich; Hedayat, Christian; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Three-dimensional particle localization with common-path digital holographic microscopy - Neutsch, Krisztian; Hofmann, Martin R.; Gerhardt, Nils Christopher; Schnitzler, Lena; Tranelis, Marlon J. (Practical Holography XXXIII: Displays, Materials, and Applications)

Semiconductor spin-lasers - Gerhardt, Nils Christopher; Žutić, Igor; Lee, Jeongsu; Gøthgen, Christian; Farla, Paulo E., Junior; Xu, Gaofeng; Sipahi, Guilherme M. (Nanoscale spintronics and applications)

Ultrafast spin-lasers - Lindemann, Markus; Xu, Gaofeng; Pusch, Tobias; Michalzik, Rainer; Hofmann, Martin R.; Žutić, Igor; Gerhardt, Nils Christopher (Nature)
Lasers have both ubiquitous applications and roles as model systems in which non-equilibrium and cooperative phenomena can be elucidated1. The introduction of novel concepts in laser operation thus has potential to lead to both new applications and fundamental insights2. Spintronics3, in which both the spin and the charge of the electron are used, has led to the development of spin-lasers, in which charge-carrier spin and photon spin are exploited. Here we show experimentally that the coupling between carrier spin and light polarization in common semiconductor lasers can enable room-temperature modulation frequencies above 200 gigahertz, exceeding by nearly an order of magnitude the best conventional semiconductor lasers. Surprisingly, this ultrafast operation of the resultant spin-laser relies on a short carrier spin relaxation time and a large anisotropy of the refractive index, both of which are commonly viewed as detrimental in spintronics3 and conventional lasers4. Our results overcome the key speed limitations of conventional directly modulated lasers and offer a prospect for the next generation of low-energy ultrafast optical communication.

Brain tissue analysis using texture features based on optical coherence tomography images - Hofmann, Martin R.; Lenz, Marcel; Krug, Robin; Gerhardt, Nils Christopher; Schmieder, Kirsten; Dillmann, Christopher; Welp, Hubert (Optical Coherence Tomography and Coherence Domain Optical Methods in Biomedicine XXII)

Classification of brain tissue with optical coherence tomography by employing texture analysis - Lenz, Marcel; Krug, Robin; Gerhardt, Nils Christopher; Schmieder, Kirsten; Hofmann, Martin R.; Dillmann, Christopher; Welp, Hubert (Optics, Photonics, and Digital Technologies for Imaging Applications V)

Digital holography for the investigation of buried structures with a common-path reflection microscope - Hofmann, Martin R.; Gerhardt, Nils Christopher; Finkeldey, Markus; Göring, Lena (Practical Holography XXXII: Displays, Materials, and Applications)

Thermally-induced birefringence in VCSELs - approaching the limits - Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Pusch, Tobias; Michalzik, Rainer; Scherübl, Sebastian (Semiconductor Lasers and Laser Dynamics VIII)